The multidimensional legal nature of personal genomic sequence data: A South African perspective - Thaldar, Donrich W.; Townsend, Beverley A.; Donnelly, Dusty-Lee; Botes, Marietjie; Gooden, Amy; van Harmelen, Joanne; Shozi, Bonginkosi (Frontiers in Genetics, 2022)
This article provides a comprehensive analysis of the various dimensions in South African law applicable to personal genomic sequence data. This analysis includes property rights, personality rights, and intellectual property rights. Importantly, the under-investigated question of whether personal genomic sequence data are capable of being owned is investigated and answered affirmatively. In addition to being susceptible of ownership, personal genomic sequence data are also the object of data subjects’ personality rights, and can also be the object of intellectual property rights: whether on their own qua trade secret or as part of a patented invention or copyrighted dataset. It is shown that personality rights constrain ownership rights, while the exploitation of intellectual property rights is constrained by both personality rights and ownership rights. All of these rights applicable to personal genomic sequence data should be acknowledged and harmonized for such data to be used effectively.